Беллона: [роман] / Анатолий Брусникин - Акунин Борис (Борис Акунин: проект "Авторы", 2012)
Экземпляры: (20180226) / Инвентарный номер: 36093 / Цена: 273.00 / Сис.шифр: Р2 / Авт.знак: А 44 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6